South Africa’s Post-Apartheid Economic and Education Reforms: A Reversal Of Racial Capitalism? - Mhonda, Takura Donald Junior (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Apartheid was a system of racial segregation that took place in South Africa. Racial segregation was institutionalised and it covered all aspects of the country. The National Party implemented a series of laws to maintain its divide and rule policy. One of the key elements used by the Apartheid regime to guarantee separate development was the education system. The Bantu education system was used to keep the non-white population at a lower status and provide a supply of cheap labour. It was one of the tools that were used to establish and maintain white supremacy in South Africa. This thesis aims to analyse the South African case from the perspective of racial capitalism. Racial capitalism emphasizes the intimate link between race and capitalism. It underlines that capitalism evolved out of feudalism as racial capitalism. Racial capitalism highlights the racial dimension of capitalism and makes a special emphasis on how capitalism was built and maintained on the exploitation of black labour. This thesis will discuss if the post-apartheid policies have contributed to the transformation of racial capitalism. It will focus on the period 1994-2018 and it will assess where things stand regarding equality in education between white and black populations. In particular, it will seek an answer to whether the post-apartheid policies empowered the black population. Keywords: racial capitalism, segregation, separate development

ÖZ: Apartheid, Güney Afrika‘da uygulanan ırksal ayrışma sistemiydi. Bu dönemde kurumsallaşan ırksal ayrışma ülkenin tüm alanlarını kapsamıştı. National Party, (Ulusal Parti) böl ve yönet politikasını sürdürülebilmek için bir dizi yasayı uygulamaya geçirmişti. Apartheid rejiminin, ayrımcı gelişimini garanti altında tutabilmek için kullandığı en önemli unsurlardan biri eğitim sistemiydi. Bantu eğitim sistemi, beyaz ırktan olmayan nüfusu daha düşük bir statüde tutmak ve ucuz iş gücü sağlamak amacı ile kullanıldı. Bu eğitim sistemi, Güney Afrika‘da beyaz ırkın egemenliğini kurmak ve sürdürmek için kullanılan araçlardan biriydi. Bu tez, Güney Afrika‘nın durumunu ırksal kapitalizm açısından analiz etmeyi amaçlamaktadır. Irkçı kapitalizm, ırk ve kapitalizm arasındaki yakın ilişkiye vurgu yapar. Kapitalizmin, feodalizmden ırkçı kapitalizm olarak geliştiğinin altını çizer. Irksal kapitalizm, kapitalizmin ırksal boyutunu vurgular ve kapitalizmin nasıl siyahi emeğin sömürülmesi üzerine kurulu olduğu üzerine özel bir vurgu yapar. Bu tez, Apartheid sonrası izlenen politikaların ırksal kapitalizmin dönüşümüne katkıda bulunup bulunmadığını tartışacaktır. 1994 - 2018 dönemine odaklanacak ve siyahi ve beyaz ırk popülasyonları arasındaki eğitimde eşitlik ile ilgili konuların nerede durduğunu değerlendirecektir. Özellikle, Apartheid sonrası izlenen politikların siyah nüfusu gerçekten güçlendirip güçlendirmediğine dair bir cevap arayacaktır. Anahtar kelimeler: ırksal kapitalizm, ayrışma, ayrı kalkınma
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2020. Supervisor: Asst. Prof. Dr. Umut Bozkurt.
Keywords: Political Science and International Relations; South Africa--Politics and government; Economic Conditions and Development--South Africa; Economic and Education Reforms--South Africa; Racial capitalism; segregation; separate development